Towards customizable thin-panel low-Z detector arrays: electrode design for increased spatial resolution ion chamber arrays - Albert, Steffen; Brivio, Davide; Aldelaijan, Saad; Sajo, Erno; Hesser, Jürgen; Zygmanski, Piotr (Physics in medicine and biology, 2020)
The purpose of the present development is to employ 3D printing to prototype an ion chamber array with a scalable design potentially allowing increased spatial resolution and a larger active area. An additional goal is to design and fabricate a custom size thin-panel detector array with low-Z components. As a proof of principle demonstration, a medium size detector array with 30 x 30 air-vented ion chambers was 3D-printed using PLA as frame for the electrodes. The active-area is 122 mm x 120 mm with 4 x 4 mm(2) spatial resolution. External electrodes are cylindrical and made from conductive PLA. Internal electrodes are made from microwire. The array is symmetric with respect to the central plane and its thickness is 10 mm including build-up/-down plates of 2.5 mm thickness. Data acquisition is realized by biasing only selected chamber rows and reading only 30 chambers at a time. To test the device for potential clinical applications, 1D dose profiles and 2D dose maps with various square and irregular fields were measured. The overall agreement with the reference doses (film and treatment planning system) was satisfactory, but the measured dose differs in the penumbra region and in the field size dependence. Both of these features are related to the thin walls between neighboring ion chambers and different lateral phantom scatter in the detector panel vs homogeneous material. We demonstrated feasibility of radiation detector arrays with minimal number of readout channels and low-cost electronics. The acquisition scheme based on selected row or column 'activation' by bias voltage is not practical for 2D dosimetry but it allows for rapid turn-around when testing of custom arrays with the aid of multiple 1D dose profiles. Future progress in this area includes overcoming the limitations due high chamber packing ratio, which leads to the lateral scattering effects.
Gesehen am 18.06.2020